Moral Communities and Sex: The Religious Influence on Young Adult Sexual Behavior and Regret. (June 2018) - Longest, Kyle C.; Uecker, Jeremy E.
Research indicates that religiosity inhibits adolescent and young adult sexual behavior, but few studies examine how religious contexts may shape sexual behavior. When religious contexts are considered, studies rarely test multiple spheres of religious influence simultaneously. Moreover, little research examines how either individual religiosity or religious contexts shape emotional responses to sex. We analyze nationally representative, longitudinal data that allow for concurrent examination of multiple religious contexts and several measures of young adult sexual behaviors and sexual regret. The influence of religiosity on sexual behavior and regret varies within and across both the spheres and outcomes tested. Individual religious salience and close ties with parents are the most consistent deterrents to initiation of sexual intercourse and having numerous intercourse partners. Closeness to parents and participation in religious activities are associated with lower odds of sexual regret, but ties to adults in one's religious congregation are associated with increased sexual regret.